Social reproduction theory : remapping class, recentering oppression - Bhattacharya, Tithi; Vogel, Lise (Pluto Press, 2017)
How do childcare, healthcare, education, family life and the roles of gender, race and sexuality affect our lives under capitalism?
Keywords: Capitalism -- Social aspects.; Consumption (Economics) -- Social aspects.; Social capital (Sociology); Social problems.; Communism.; Social Problems; Capital social (Sociologie); Problèmes sociaux.; Société de consommation -- Aspect social.; social issues.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Capitalism -- Social aspects; Communism; Consumption (Economics) -- Social aspects; Social problems; Electronic book.